2023
DOI: 10.7759/cureus.35754
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Causes and Complications of ST-Segment Myocardial Infarction That Highlight the Importance and Limitations of Point-of-Care Ultrasound in the Emergency Department

Abstract: Point-of-care transthoracic echocardiography is a valuable tool for Emergency Physicians evaluating a patient in shock. We describe a case report of ST-segment myocardial infarction complicated by cardiogenic shock and acute severe mitral valve regurgitation that was immediately identified by the Emergency Physician. However, subsequent testing revealed an unexpected unifying diagnosis. The diagnostic sequence in this case highlights the benefits and limitations of point-of-care ultrasound in the Emergency Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Nevertheless, Arntfield et al [41] and Millington et al [44] concluded that PoCE served as an indispensable instrument for the diagnosis and treatment of acute cardiac conditions, including valvular emergencies. Similarly, Johnson et al [45] affirmed the value of PoCE as a vital apparatus for emergency physicians assessing patients in shock.…”
Section: Hope For Left-sided Cardiac Valve Evaluationmentioning
confidence: 96%
“…Nevertheless, Arntfield et al [41] and Millington et al [44] concluded that PoCE served as an indispensable instrument for the diagnosis and treatment of acute cardiac conditions, including valvular emergencies. Similarly, Johnson et al [45] affirmed the value of PoCE as a vital apparatus for emergency physicians assessing patients in shock.…”
Section: Hope For Left-sided Cardiac Valve Evaluationmentioning
confidence: 96%